A33 Travel behaviour change in the transition to adulthood: Insights from a biographical study. Issue 2 (June 2015) - Jones, Heather; Chatterjee, Kiron
Abstract: Background: The decline in driver licence acquisition and car use among younger adults in Great Britain in recent decades could be indicative of wider changes in travel behaviour for this age group, including a greater amount of walking and cycling. Studies which illuminate individual developments in travel behaviour through the period of transition to adulthood can interpret and explain the aggregate trends and societal changes contributing to this. Methods: Thirty-three qualitative interviews were conducted with individuals, drawn from two birth cohorts (born 1945-55 and 1975-85), and located in the Bristol area in south-west England. From these were constructed retrospective biographical accounts of travel behaviour. Analysis was an iterative process examining the common and distinct developments of travel behaviour in relation to life transitions in early adulthood. Inter-cohort comparisons were made to identify how changes over time in the occurrence and timing of events in early adult lives might be influencing take up or departure from different travel behaviour trajectories. Results: The younger cohort demonstrated a general tendency for car use to commence with entry to employment. Walking, public transport and in some cases cycling were the principal modes of transport at higher education. There was some continuity in these travel behaviours after higher education. Employment or residential changes sometimes brought returns to these forms of mobility early in graduate careers. By comparison their peers who did not go to university were consistent in a shift to car driving with entry to employment. Their early careers were characterised by shift work, peripheral employment locations and work that involved travel. Amongst the older cohort it was gender differences in car access rather than higher education that differentiated the cohort; women were generally later in acquiring the means of driving and as a result had greater experience of walking, using public transport and getting lifts, with some use of bikes. Conclusions: The comparison of birth cohorts helps to understand the implications of societal changes in the timings and occurrences of life course for travel behaviour patterns and identify opportunities to shape trajectories of travel behaviour in the long term. This particular study suggests the need to confirm and then, if necessary, attend to an apparent disadvantage amongst young adults who do not attend higher education or pursue graduate careers to develop non-car based styles of mobility.